A chronological review of prospects of solar photovoltaic systems in Bangladesh: Feasibility study analysis, policies, barriers, and recommendations. Issue 10 (20th April 2021) - Podder, Amit Kumer; Habibullah, Md.; Roy, Naruttam Kumar; Pota, Hemanshu Roy
Abstract: The main focus of this paper is to present the current prospects, potentials, research activities, future concerns, and applications of solar photovoltaic (PV) systems in Bangladesh. Despite the existence of several articles in the literature on solar energy prospects in Bangladesh, the diffusion of several solar PV applications throughout the country, their rapid progress analysis, and existing feasibility study outcome analysis are still unrevealed. Therefore, an endeavour has been made for the first time to condense the government and non‐government contributions to disseminating solar energy throughout the country. Twenty‐one feasibility studies at different locations of Bangladesh are reviewed and analysed, in terms of financial viability, sensitivity analysis, and greenhouse gas emissions, to foresee the prospects of solar energy in Bangladesh. Sensitivity analyses are performed, with six sensitivity variables, which reveal that the total net present cost of the solar project implementation may be increased by 20% (maximum) in the lowest solar potential area than the highest one with an average payback period of 13 years. This paper also identifies the policy gaps, classifies the barriers into eight categories, and discusses the conceivable approaches to defeat those barriers, followed by recommendations in six different aspects.